Tackling the barriers in open innovation practices in emerging markets ; An evidence-based framework from Turkey, Russia and India - Riihimäki, Joni Mikael (My University, 2021)
Open innovation can be anticipated to be a part of new pattern for the innovation management as it includes controlling inbound, outbound and coupled movements among open innovation network. Furthermore, this approach highlights the role of usage a wide variety of external knowledge bases while handling this kind of activities brings out individual challenges especially when more actors are connected into innovation network. At some stage, challenges or barriers like negative attitude, lack of resources, fear of sharing confidential information and communication difficulties may arise among open innovation actors towards open innovation. Within the scope of possible trends around the economic cycle, companies have started to notice the benefits and opportunities of openness which is resulted from the nature of current globalized and technological based environment. Additionally, the literature around open innovation has covered well the benefits in both SMEs and large enterprises while bringing out different challenges which companies may face. However, negative topics around open innovation are highly unstudied while certain papers focus only on certain challenges like negative attitude and managerial prospects. This investigative paper examines different challenges which SMEs and large enterprises face both before and during the open innovation activities. Furthermore, the survey focuses on finding out possible ways to overcome these while also mapping the success rate between different collaborators in terms of innovation success. In the survey, the share of challenges faced are measured with eleven possible challenges which companies may have faced in their open innovation activities during the last five years. The results of research points out that regardless the size of the company or industry, companies tend to see value in innovation activities. However, based on 196 survey participants unique trend on fear of sharing confidential knowledge in every subgroup can be highlighted while it was the most commonly faced challenge both before and during the open innovation activities. Additionally, the role of negative attitude cannot be dismissed while it had increasing trend among the survey respondents. In order to overcome possible challenges and barriers of open innovation activities, three different frameworks were created. In overall, literature around this theme does not consist enough frameworks for coping with variety of open innovation challenges. From this point of view, academia linkage to variety of possible challenges faced needs to be strengthened. Furthermore, it is found that open innovation activities with customers are at the same time the most popular and successful choice while competitors possessed the least successful position among other external collaborators.

Avoimen innovaation voidaan ennakoida tulevan osa uutta innovaatiohallinnan mallia, joka sisältää sisäänpäin, ulospäin ja yhteistyöhön suuntautuvien toimintojen ohjaamista avoimen innovaatioverkoston välillä. Lisäksi tässä lähestymistavassa korostetaan erilaisten ulkoisten tietoperustojen käytön merkitystä, kun taas tällaisten toimien käsittely tuo esiin haasteita erityisesti samalla, kun useammat toimijat ovat yhteydessä innovaatioverkostoon. Avoimeen innovointiin tähtäävien avointen innovointikumppaneiden keskuudessa voi jossain vaiheessa syntyä haasteita tai esteitä kuten kielteinen asenne, resurssien puute, luottamuksellisen tiedon jakamisen pelko ja kommunikointivaikeudet. Taloudellisen suhdanteen mahdollisten suuntausten puitteissa, yritykset ovat alkaneet havaita avoimuuden edut ja mahdollisuudet, joka johtuu nykyisen globalisoituneen ja teknologisen ympäristön luonteesta. Lisäksi avoimen innovoinnin kirjallisuus on kattanut hyvin sekä pk-yritysten että suurten yritysten hyödyt ja tuonut esiin erilaisia yksittäisiä haasteita, joita yritykset voivat kohdata. Avoimen innovaation ympärillä olevat negatiiviset aiheet ovat kuitenkin erittäin kartoittamattomia, kun taas tietyissä tutkimuspapereissa keskitytään vain yksittäisiin haasteisiin kuten negatiiviseen asenteeseen ja johtonäkymiin. Tässä tutkivassa paperissa tarkastellaan erilaisia haasteita, joita pk-yritykset ja suuret yritykset kohtaavat sekä ennen avointa innovaatiotoimintaa että sen aikana. Lisäksi kyselyssä keskitytään selvittämään mahdollisia keinoja selviytyä näistä haasteista ja kartoittaa eri yhteistyökumppaneiden välistä onnistumisastetta innovoinnin menestyksen kannalta. Kyselyssä haasteiden osuutta mitataan yhdellätoista mahdollisella haasteella, joita yritykset ovat saattaneet kohdata avoimessa innovaatiotoiminnassaan viimeisen viiden vuoden aikana. Tutkimustulokset tuovat esiin, että yrityksen koosta tai toimialasta riippumatta yritykset näkevät innovaatiotoiminnassa yleensä arvoa. Kuitenkin, tutkimuksen 196 osallistujan perusteella voidaan korostaa ainutlaatuinen trendi luottamuksellisen tiedon jakamisen pelosta jokaisessa alaryhmässä, sillä se oli yleisimmin kohdattu haaste sekä ennen avointa innovaatiotoimintaa että sen aikana. Tämän ohella, kielteisen asenteen roolia ei voida hylätä, sillä se oli kasvussa kyselyyn vastanneiden keskuudessa. Avoimen innovaatiotoiminnan mahdollisten haasteiden ja esteiden voittamiseksi luotiin kolme erilaista kehystä. Kaiken kaikkiaan tämän teeman ympärillä oleva kirjallisuus ei sisällä riittävästi kehyksiä erilaisten avoimen innovaatiohaasteiden ratkaisemiseen. Tästä näkökulmasta, akateemisen maailman yhteyksiä erilaisiin mahdollisiin haasteisiin on vahvistettava. Lisäksi todetaan, että avoin innovaatiotoiminta asiakkaiden kanssa on samalla suosituin ja menestyksekkäin valinta, kun taas kilpailijoilla on vähiten onnistunein asema muiden sidosryhmien keskuudessa.
Keywords: emerging markets; innovation (activity); challenges; barriers; openness; innovation systems; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management; Technology Management and Product Development